2001
DOI: 10.1046/j.1365-2249.2001.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone impairs pulmonary defence againstPseudomonas aeruginosathrough suppressing iNOS gene expression and peroxynitrite production in mice

Abstract: SUMMARYTo elucidate the in vivo mechanisms involved in the impairment in pulmonary defence as the result of treatment with glucocorticoids, we established fatal pneumonia with bacteraemia in dexamethasone (DEX)-treated mice by means of an intratracheal challenge of Pseudomonas aeruginosa. An increased neutrophil influx was observed in bronchoalveolar lavage (BAL) fluids from both untreated and DEXtreated mice. The complete suppression of an inducible isoform of nitric oxide synthase (iNOS) mRNA expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
1
27
0
2
Order By: Relevance
“…To determine whether P. aeruginosa-induced MC IL-1␣ and IL-1␤ can be regulated, dexamethasone and IL-10 were chosen because corticosteroids and IL-10 have been directly or indirectly implicated in P. aeruginosa infection (42)(43)(44)(45)(46). We demonstrated that dexamethasone markedly inhibited P. aeruginosa-induced IL-1␣, IL-1␤, as well as TNF-␣ production by human MC.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To determine whether P. aeruginosa-induced MC IL-1␣ and IL-1␤ can be regulated, dexamethasone and IL-10 were chosen because corticosteroids and IL-10 have been directly or indirectly implicated in P. aeruginosa infection (42)(43)(44)(45)(46). We demonstrated that dexamethasone markedly inhibited P. aeruginosa-induced IL-1␣, IL-1␤, as well as TNF-␣ production by human MC.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, corticosteroids have demonstrated a beneficial effect on pulmonary function in CF patients with chronic P. aeruginosa infection (46). However, the multiple targets other than MC of IL-10 and dexamethasone may not always be beneficial should the IL-10 or dexamethasone overly suppress normal host defenses (42,44). The adverse effects of corticosteroids due to their nonspecific immunosuppressive actions limit their application in CF patients (50).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is feasible that Ohr plays a relevant role in vivo in the reduction of peroxynitrite. This role might be significant, especially considering that inducible nitric oxide synthase (and possibly peroxynitrite as a product of nitric oxide) displays a crucial role in the pulmonary response to P. aeruginosa infection (42,56). Also for plant pathogens (e.g., X. fastidiosa), peroxynitrite and other nitric oxide-mediated processes are emerging as relevant players in defense responses (41).…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots of 100 μL of 24 h old dexamethasone-adapted cells containing ca. 1×10 8 CFU mLG 1 were transferred to wells and the plates were incubated for 2 h, at 37°C and 150 rpm. The wells were drained by aspiration and gently washed once with sterile water.…”
Section: Cell Surface Hydrophobicity (Csh)mentioning
confidence: 99%
“…This molecule is used as anti-inflammatory and anti-allergic drug, usually prescribed on the treatment of cystic fibrosis. However, available data about the interplay between dexamethasone and P. aeruginosa infection shows that high doses of glucocorticoid may impair pulmonary host defense by increasing bacterial density 8 . By other side, it is practically impossible to avoid the exposition of a pathogen as P. aeruginosa after the xenobiotic intake 9 .…”
Section: Introductionmentioning
confidence: 99%